1993
DOI: 10.1172/jci116541
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and hyperinsulinemia in individuals with small, dense low density lipoprotein particles.

Abstract: Subjects characterized by a predominance of small LDL particles (pattern B) have changes in plasma triglyceride (TG) and HDL-cholesterol concentrations consistent with the presence of resistance to insulin-mediated glucose uptake. To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
271
3
11

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 630 publications
(298 citation statements)
references
References 29 publications
13
271
3
11
Order By: Relevance
“…The variable most closely related to LDL particle size in the present study was plasma triglyceride levels (rZ0.372, P!0.001) as previously reported (41). At present, the reason why LDL particle size was elevated in Asp298 allele carriers cannot be explained.…”
Section: Discussionsupporting
confidence: 85%
“…The variable most closely related to LDL particle size in the present study was plasma triglyceride levels (rZ0.372, P!0.001) as previously reported (41). At present, the reason why LDL particle size was elevated in Asp298 allele carriers cannot be explained.…”
Section: Discussionsupporting
confidence: 85%
“…The unique findings of the present study are that subjects with metabolic syndrome identified by clinically applicable criteria showed an independent association with LDL-C to influence on carotid IMT. Hulthe et al (29) reported that subjects with metabolic syndrome had an increased carotid IMT compared to that of subjects with no risk factors, and components of the metabolic syndrome such as insulin resistance, dyslipidemia, and glucose intolerance are significantly associated with increasing LDL-C (30) and also related to small LDL particles (31)(32)(33). In addition, LDL-C (12) and small LDL particle sizes are also associated with the occurrence and size of plaques in the carotid artery (29).…”
Section: Disucussionmentioning
confidence: 99%
“…7 -11 Adverse effects of insulin resistance on lipid metabolism, with consequent effects on circulating TAG concentrations, may be the primary metabolic defect that leads to low HDL and increased prevalence of small dense LDL, 12,13 which are the key features of the atherogenic lipoprotein phenotype. 14 Greater tendency for central fat deposition after the menopause may be particularly relevant to the higher incidence of CHD in post-menopausal women, since, although central obesity has been shown to be a strong risk factor for both men and women, studies in women generally produce values for relative risk that are higher than those found in men.…”
Section: Introductionmentioning
confidence: 99%